2010
DOI: 10.1111/j.1600-051x.2010.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between calcium channel blockers and gingival hyperplasia

Abstract: This study shows that the risk of gingival hyperplasia is twofold higher in current users of CCBs than in users of RAS drugs. The association was dose dependent and the highest for dihydropyridines or benzothiazepine derivates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
0
24
0
5
Order By: Relevance
“…[3334] Synergistic effects have been reported when cyclosporin is administered concurrently with calcium channel blockers of dihydropyridine derivatives. [35]…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…[3334] Synergistic effects have been reported when cyclosporin is administered concurrently with calcium channel blockers of dihydropyridine derivatives. [35]…”
Section: Drugs Which Cause Gingival Overgrowthmentioning
confidence: 99%
“…KKB ve CsA'nın jinjival hiperplaziye neden olduğu bilinmektedir. 53,54 Her ne kadar jinjival hiperplazi tanısı olan iki olguda da ilaç etyolojik faktör olarak görülse de, hasta sayısının az olması nedeniyle bu ilişki istatistiksel düzeyde anlamlı olarak sonuçlan-madı. Çalışmamızda ayrıca, araştırdığımız dermatolojik hastalıklar ve OML ilişkisinde istatistiksel düzeyde yalnızca akne grubu hastalıklar ile keilit gelişimi arasında anlamlılık tespit edildi, bu bulgunun da izotretinoin tedavisi alanlarda görülen ilaca bağlı keilit nedeniyle ortaya çıktığı düşüncesinde-yiz.…”
Section: Discussionunclassified
“…Some studies showed an association between the use of CCBs and gingival hyperplasia (29, 30). Two main inflammatory and non-inflammatory pathways have been already suggested.…”
Section: Discussionmentioning
confidence: 99%